Hospital Mechanical Ventilation Volume and Patient Outcomes: Too Much of a Good Thing?. Issue 3 (March 2019) - Mehta, Anuj B.; Walkey, Allan J.; Curran-Everett, Douglas; Matlock, Daniel; Douglas, Ivor S.
Abstract : Objectives: Prior studies investigating hospital mechanical ventilation volume-outcome associations have had conflicting findings. Volume-outcome relationships within contemporary mechanical ventilation practices are unclear. We sought to determine associations between hospital mechanical ventilation volume and patient outcomes. Design: Retrospective cohort study. Setting: The California Patient Discharge Database 2016. Patients: Adult nonsurgical patients receiving mechanical ventilation. Interventions: The primary outcome was hospital death with secondary outcomes of tracheostomy and 30-day readmission. We used multivariable generalized estimating equations to determine the association between patient outcomes and hospital mechanical ventilation volume quartile. Measurements and Main Results: We identified 51, 689 patients across 274 hospitals who required mechanical ventilation in California in 2016. 38.2% of patients died in the hospital with 4.4% receiving a tracheostomy. Among survivors, 29.5% required readmission within 30 days of discharge. Patients admitted to high versus low volume hospitals had higher odds of death (quartile 4 vs quartile 1 adjusted odds ratio, 1.40; 95% CI, 1.17–1.68) and tracheostomy (quartile 4 vs quartile 1 adjusted odds ratio, 1.58; 95% CI, 1.21–2.06). However, odds of 30-day readmission among survivors was lower at high versus low volume hospitals (quartile 4 vs quartile 1 adjusted odds ratio, 0.77; 95% CI, 0.67–0.89). Higher hospital mechanical ventilation volume was weakly correlated with higher hospital risk-adjusted mortality rates ( ρ = 0.16; p = 0.008). These moderately strong observations were supported by multiple sensitivity analyses. Conclusions: Contrary to previous studies, we observed worse patient outcomes at higher mechanical ventilation volume hospitals. In the setting of increasing use of mechanical ventilation and changes in mechanical ventilation practices, multiple mechanisms of worse outcomes including resource strain are possible. Future studies investigating differences in processes of care between high and low volume hospitals are necessary. Abstract : Supplemental Digital Content is available in the text.